Children in Custody Disputes Matching Legal Proceedings to Problems - Kaldal, Anna; Hellner, Agnes; Mattsson, Titti (Springer Nature, 2024)
​This open access book explores how legal proceedings in and out-of-court can be matched to the complex problems underlying disputes concerning child custody, residence and contact between parents. It focusses in particular on Nordic experiences of in and out-of-court mechanisms as means of resolving custody disputes. The contributors are internationally renowned and experienced researchers from the legal, psychological, and sociological fields who provide empirical as well as legal perspectives. They examine central legal, ethical and knowledge-based dilemmas in custody dispute proceedings. The findings speak to an international audience and suggest ways how to best realize the interests of the child. It transcends disciplinary, institutional, and jurisdictional boundaries in search of new knowledge.